1997
DOI: 10.1046/j.1365-2796.1997.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metformin on blood pressure and metabolism in nondiabetic hypertensive patients

Abstract: Results. The possible effect of metformin treatment and dosage was tested with a two-factor analysis of variance. Treatment induced a significant decline in diastolic oBP, P Ͻ 0.05. This decline was, however, not significantly different comparing metformin and placebo. Systolic oBP, diastolic aBP, and systolic aBP showed no significant change by treatment. The decline in diastolic oBP was 5 mmHg in the pooled group of metformin-treated patients, P Ͻ 0.005. Different gender and the presence of obesity had no im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Administration of 500-850 mg metformin twice daily for 12 weeks lowered diastolic blood pressure in 25 nondiabetic hypertensive persons, but not significantly more than placebo did [40].…”
Section: Metformlnmentioning
confidence: 85%
“…Administration of 500-850 mg metformin twice daily for 12 weeks lowered diastolic blood pressure in 25 nondiabetic hypertensive persons, but not significantly more than placebo did [40].…”
Section: Metformlnmentioning
confidence: 85%
“…In the literature, information is scarce regarding C peptide secretion after metformin treatment in groups of patients with normal glucose tolerance and insulin resistance (as women with PCOS mostly have). We are aware of a study (31) finding no change in either basal or stimulated levels of C peptide in a group of hypertensive patients after metformin. In a group of obese type 2 diabetics an increase in C peptide levels after metformin treatment was found (32).…”
Section: ) Although Not With Those Obtained By Others (12± 15)mentioning
confidence: 97%
“…Acta Pharmacologica Sinica npg effect on blood pressure in non-diabetic hypertensives [17] . We previously reported that metformin inhibited cardiac fibrosis in the TAC-mouse model and demonstrated that it inhibited collagen synthesis, likely via inhibition of the TGF-β 1 -Smad3 signaling pathway [18] .…”
Section: Wwwchinapharcom Fu Yn Et Almentioning
confidence: 99%